Antistatic master batch and preparation method thereof
By preparing an antistatic masterbatch composed of PVA resin, maleic anhydride graft or copolymer, the problem of lack of antistatic masterbatch with moderate price and excellent precipitation resistance in the prior art is solved, and efficient and environmentally friendly antistatic properties are achieved.
Patent Information
- Application Number
- CN202510266029.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-07
- Publication Date
- 2025-05-09
AI Technical Summary
The existing market lacks affordable, excellent precipitation resistance, and is difficult to popularize and apply in the industry.
An antistatic masterbatch is used, which consists of PVA resin, maleic anhydride graft or copolymer, organic alkali metal salt oligomer, plasticizer, anti-decomposition agent, metal silicate or carbonate and other additives, and is prepared through specific process steps to achieve the improvement of electrical conductivity and precipitation resistance.
It realizes anti-static masterbatches with low cost, good conductivity, excellent precipitation resistance, and excellent sterilization and mildew resistance, which are suitable for large-scale industrial production.
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] The invention relates to the field of polymer composites, and in particular to an antistatic masterbatch and a preparation method thereof. Background Art
[0002] The mainstream antistatic products on the market are mainly achieved by adding conductive fillers, adding low-molecular antistatic agents, applying conductive coatings, and intrinsically conductive polymer alloys, but these methods all have some defects. For example, the color of antistatic materials filled with conductive carbon black can only be limited to black, and the products have a tendency to decarbonize, which poses a potential risk to the packaging of electronic components with high cleanliness requirements; the antistatic performance of products added with low-molecular antistatic agents has high requirements on the humidity of the environment and has a certain timeliness; the antistatic materials coated with antistatic coatings have a more complicated implementation method, high cost, and a long production cycle. The antistatic coating is easy to fall off and damage, which affects the appearance of the product and the antistatic performance will disappear; the antistatic materials made by adding intrinsic conductive polymer materials such as polyaniline have a large addition amount, poor comprehensive physical properties and high cost.
[0003] In recent years, foreign countries have compounded polymer antistatic agents based on polyetheramide block copolymers and polyetherester block copolymers, such as the polymer antistatic agent Irgastat P18 developed by BASF, PVL and AS of Sanyo Chemical of Japan, etc. These antistatic agents have the advantages of long-lasting antistatic effect, small addition amount, light color, etc., but the price is too high to be widely used in industry. Therefore, how to make natural color permanent antistatic masterbatch with moderate price and adapt to the market demand has become a difficult problem that needs to be solved urgently in China.
[0004] Patent CN102061050B mentions the use of low dissociation energy compounding agents such as alkali metal perchlorate, alkali metal thiocyanate, alkali metal fluoroborate, alkali metal hexafluorophosphate, alkali metal trifluoromethanesulfonic acid, imidazole-type ionic liquid salts, pyridine-type ionic liquid salts and other small molecule salts as donors of conductive ions, and polar polymer resins as carriers. Small molecule salts are not easy to disperse evenly and are easy to precipitate on the surface, which will cause pollution or corrosion damage to the packaged objects.
[0005] Patent CN114829502B mentions an antistatic agent (Z) containing a block polymer (A) and a sulfonate (S). The block polymer (A) has a block of a hydrophobic polymer (a) and a block of a hydrophilic polymer (b) as structural units. The sulfonate (S) is a salt composed of an alkyl (the alkyl group has 6 to 18 carbon atoms) benzenesulfonate anion. The precipitation resistance of long-chain branched benzenesulfonates is greatly improved compared with small molecule salts, but the block polymer process is complicated and the cost is relatively high. Summary of the invention
[0006] In order to overcome the shortcomings of the background technology, the present invention provides an antistatic masterbatch and a preparation method thereof, which mainly solves the problem that there is no natural antistatic masterbatch with good precipitation resistance and moderate price in the current market.
[0007] The technical solution of the present invention is: An antistatic masterbatch comprises the following components by weight: 40 to 60 parts of PVA resin; Maleic anhydride graft or copolymer 10-40 parts 2-10 parts of organic alkali metal salt oligomer Plasticizer 10-15 parts Antidegradant 0.5~5 parts 3-7 parts of metal silicate or carbonate The rest are other additives.
[0008] The PVA resin has an alcoholysis degree of 88%-100%, wherein the PVA with an alcoholysis degree of 88% accounts for 3%-6%, and the PVA with an alcoholysis degree of 99% accounts for 94%-97%.
[0009] The metal silicate is a silicate of calcium, magnesium, aluminum, potassium, sodium or a carbonate of calcium, magnesium, aluminum, potassium, sodium.
[0010] The monomer of the organic alkali metal salt oligomer is p-styrene sulfonate, and the alkali metal ion is one or more of Li+, Na+, and K+.
[0011] The metal silicate is a mineral with a two-dimensional nanosheet structure.
[0012] The plasticizer is one or a mixture of ethylene glycol and its polymers, propylene glycol and its polymers, and fatty amine polyoxyethylene ether.
[0013] The average polymerization degree of the PVA resin is 300-2700.
[0014] The degree of polymerization of the organic alkali metal salt oligomer is 5-20, preferably 6-10.
[0015] The anti-decomposition agent is alcohol ether phosphate.
[0016] The other auxiliary agent is an antioxidant.
[0017] A method for preparing the antistatic masterbatch as described above comprises the following steps: Step 1, preparing the oligomer of styrene sulfonate: 3-6 parts of PVA, 100-200 parts of deionized water, 10-30 parts of styrene sulfonate, controlling the reaction time to 4-6 hours, the temperature to 25-30° C., to obtain a solution a of the oligomer of styrene sulfonate with a degree of polymerization in the range of 5 to 20; Step 2, add 10-30 parts of one or more mixtures of glycerol, ethylene glycol and polymers thereof, propylene glycol and polymers thereof and fatty amine polyoxyethylene ether, and 0.5-5 parts of alcohol ether phosphate to solution a, stir evenly, then add 94-97 parts of PVA resin, heat and stir to 50-70° C., keep warm for 30-60 minutes, heat and stir again to raise the temperature to 95-100° C. and keep warm for 1-2 hours to obtain mixture b; Step 3, add 1 to 20 parts of metal silicate or metal carbonate to solution b, stir evenly, maintain the temperature at 100°C and dry to constant weight, put into an internal mixer, control the temperature at 120-130°C, reduce pressure and plasticize, and crush to obtain material c; material c is mixed with 20-80 parts of maleic anhydride grafted or copolymerized polymer, and then reacted, extruded and granulated to obtain a colorable permanent antistatic masterbatch d.
[0018] In the step 1, the polymerization degree of the oligomer of styrene sulfonate is 5 to 20; and the alcoholysis degree of PVA is 80% to 96%.
[0019] The step 1 also includes a catalyst ferric chloride and a co-catalyst pentamethyldiethylenetriamine and ammonium chloride, and is catalyzed by ultraviolet light.
[0020] The alcoholysis degree of the PVA resin in the step 3 is 99-100%.
[0021] The beneficial effects of the present invention are as follows: the present invention provides an antistatic masterbatch and a preparation method thereof, the whole production process does not discharge waste such as solvents, the intermediate products are generated in situ, are evenly distributed, are utilized on site, and are environmentally friendly and efficient; according to the type of polymer grafted or copolymerized with maleic anhydride, a matrix resin with good compatibility with the antistatic masterbatch is determined for mixed melt processing and molding, and the application can cover most general resins, such as PP, PE, POE and other reaction extrusion granulation products grafted with maleic anhydride can adapt to most non-polar resins, and SMA and other reaction extrusion granulation products can adapt to ABS, PC, PA6, PBT most polar resins, etc. The antistatic masterbatch of the present invention has low cost, good conductivity, excellent precipitation resistance, excellent sterilization and mildew resistance, and is easy to realize large-scale industrial production. DETAILED DESCRIPTION
[0022] The present invention is further described below. An antistatic masterbatch comprises the following components in parts by weight: 40 to 60 parts of PVA resin; Maleic anhydride graft or copolymer 10-40 parts 2-10 parts of organic alkali metal salt oligomer Plasticizer 10-15 parts Antidegradant 0.5~5 parts 3-7 parts of metal silicate or carbonate The rest are other additives.
[0023] The PVA resin has an alcoholysis degree of 88%-100%, wherein the PVA with an alcoholysis degree of 88% accounts for 3%-6%, and the PVA with an alcoholysis degree of 99% accounts for 94%-97%.
[0024] The average polymerization degree of the PVA resin is 500-1700, such as 0588, 0599, 1788, 1799, etc., and 1788 and 1799 are preferred for antistatic properties.
[0025] The metal silicate is a silicate of calcium, magnesium, aluminum, potassium, sodium or a carbonate of calcium, magnesium, aluminum, potassium, sodium.
[0026] The monomer of the organic alkali metal salt oligomer is p-styrene sulfonate, and the alkali metal ion is one or more of Li+, Na+, and K+. Considering the antistatic performance and cost, Li+ and Na+ are preferred.
[0027] The anti-decomposition agent is alcohol ether phosphate, RO (CH2CH2O) n -PO(OH)2 and [RO(CH2CH2O) n ]2PO(OH)R:C=12-14n= 3, 9, RO(CH2CH2O) is preferred in terms of compatibility and heat resistance n -PO(OH)2R:C=14n=9.
[0028] The metal silicate is a mineral with a two-dimensional nanosheet structure, such as montmorillonite, kaolin, diatomaceous earth and mica. For antistatic performance, montmorillonite and kaolin are preferred, and the particle size is preferably less than 1 μm, and more preferably D50 is 500 nm.
[0029] The other auxiliary agents are well known, such as antioxidants tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate] pentaerythritol ester, triphenyl phosphite, etc., lubricants calcium stearate, zinc, etc., ultraviolet absorbers [2-(2-hydroxy-5-methylphenyl)benzotriazole, etc.
[0030] The plasticizer is a mixture of one or more of ethylene glycol and its polymers, glycerol and its polymers, and fatty amine polyoxyethylene ether. In terms of plasticizing effect and precipitation resistance, polymers of the two types of alcohols are preferred, and more preferably, the degree of polymerization is 2-20.
[0031] A method for preparing the antistatic masterbatch as described above comprises the following steps: The following steps are involved: Step 1, preparing the oligomer of styrene sulfonate: 3-6 parts of PVA, 100-200 parts of deionized water, 10-30 parts of styrene sulfonate, controlling the reaction time to 4-6 hours, the temperature to 25-30° C., to obtain a solution a of the oligomer of styrene sulfonate with a degree of polymerization in the range of 5 to 20; Step 2, add 10-30 parts of one or more mixtures of glycerol, ethylene glycol and polymers thereof, propylene glycol and polymers thereof and fatty amine polyoxyethylene ether, and 0.5-5 parts of alcohol ether phosphate to solution a, stir evenly, then add 94-97 parts of PVA resin, heat and stir to 50-70° C., keep warm for 30-60 minutes, heat and stir again to raise the temperature to 95-100° C. and keep warm for 1-2 hours to obtain mixture b; Step 3, add 1 to 20 parts of metal silicate or metal carbonate to solution b, stir evenly, maintain the temperature at 100°C and dry to constant weight, put into an internal mixer, control the temperature at 120-130°C, reduce pressure and plasticize, and crush to obtain material c; material c is mixed with 20-80 parts of maleic anhydride grafted or copolymerized polymer, and then reacted, extruded and granulated to obtain a colorable permanent antistatic masterbatch d.
[0032] In the step 1, the polymerization degree of the oligomer of styrene sulfonate is 5 to 20; and the alcoholysis degree of PVA is 80% to 96%.
[0033] The step 1 also includes a catalyst ferric chloride and a co-catalyst pentamethyldiethylenetriamine and ammonium chloride, and is catalyzed by ultraviolet light.
[0034] The alcoholysis degree of the PVA resin in the step 3 is 99-100%.
[0035] Example 1 300 g of PVA0588, 10000 g of deionized water, 1000 g of sodium p-methylstyrene sulfonate, appropriate amounts of catalysts such as ferric chloride, pentamethyldiethylenetriamine and ammonium chloride, and a molecular weight regulator such as 2-hydroxyethyl 2-bromoisobutyrate were placed in a 50 L reactor, stirred, and catalyzed by ultraviolet light. The reaction time was controlled to be 4-6 hours and the temperature was 25-30° C. to obtain a solution a1 of oligomers of sodium styrene sulfonate with a degree of polymerization of 8 to 10. Add 400g of diethylene glycol, 600g of polyglycerol decaglycerol, and 50g of alcohol ether phosphate MOA-9P to solution a1, stir evenly, then add 11700g of PVA1799 resin and 10000g of deionized water, heat and stir to 60°C, keep warm for 30 minutes, then heat and stir to 95-100°C and keep warm for 1-2 hours to obtain solution b1 Add 1000 g of montmorillonite with a D50 of 400-500 nm to solution b1, stir evenly, maintain the temperature at 100°C-110°C and dry under reduced pressure until constant weight, put into a 50L internal mixer, control the temperature at 120-130°C, plasticize under reduced pressure, and crush to obtain material c1; Divide material c1 into 2 parts on average, mix one part with 3kg of maleic anhydride grafted PP with a grafting rate of 1.2%, and then react and extrude it into granules. The temperature is controlled at 160℃-220℃, and the reaction time is 60-70 seconds to obtain colorable permanent antistatic masterbatch d11; the other part is mixed with 3kg of SMA-700 (maleic anhydride content of 18%), and then react and extrude it into granules. The temperature is controlled at 170℃-220℃, and the reaction time is 50-60 seconds to obtain colorable permanent antistatic masterbatch d12.
[0036] Example 2 600 g of PVA0588, 10000 g of deionized water, 1000 g of sodium p-methylstyrene sulfonate, appropriate amounts of catalysts such as ferric chloride, pentamethyldiethylenetriamine and ammonium chloride, and a molecular weight regulator such as 2-hydroxyethyl 2-bromoisobutyrate were placed in a 50 L reactor, stirred, and catalyzed by ultraviolet light. The reaction time was controlled to be 4-6 hours and the temperature was 25-30° C. to obtain a solution a2 of oligomers of sodium styrene sulfonate with a degree of polymerization ranging from 6 to 8. Add 400g of diethylene glycol, 600g of polyglycerol decaglycerol, and 50g of alcohol ether phosphate MOA-9P to solution a2, stir evenly, then add 11400g of PVA1799 resin and 10000g of deionized water, heat and stir to 60°C, keep warm for 30 minutes, heat and stir again to 95-100°C and keep warm for 1-2 hours to obtain solution b2 Add 1000 g of montmorillonite with a D50 of 400-500 nm to solution b, stir evenly, maintain the temperature at 100°C-110°C and dry under reduced pressure until constant weight, put into a 50L internal mixer, control the temperature at 120-130°C, plasticize under reduced pressure, and crush to obtain material c2; Divide material c2 into 2 parts, one part is mixed with 3kg of maleic anhydride grafted PP with a grafting rate of 1.2%, and then reacted by extrusion granulation. The temperature is controlled at 160℃-220℃ and the reaction time is 60-70 seconds to obtain colorable permanent antistatic masterbatch d21; the other part is mixed with 3kg of SMA-700 (maleic anhydride content of 18%), and then reacted by extrusion granulation. The temperature is controlled at 170℃-220℃ and the reaction time is 50-60 seconds to obtain colorable permanent antistatic masterbatch d22.
[0037] Example 3 500 g of PVA0588, 10000 g of deionized water, 1200 g of sodium p-methylstyrene sulfonate, appropriate amounts of catalysts such as ferric chloride, pentamethyldiethylenetriamine and ammonium chloride, and a molecular weight regulator such as 2-hydroxyethyl 2-bromoisobutyrate were placed in a 50 L reactor, stirred, and catalyzed by ultraviolet light. The reaction time was controlled to be 4-6 hours and the temperature was 25-30° C. to obtain a solution a3 of oligomers of sodium styrene sulfonate with a polymerization degree of 9 to 10. Add 400g of diethylene glycol, 600g of polyglycerol decaglycerol, and 50g of alcohol ether phosphate MOA-9P to solution a3, stir evenly, then add 11500g of PVA1799 resin and 10000g of deionized water, heat and stir to 60°C, keep warm for 30 minutes, then heat and stir to 95-100°C and keep warm for 1-2 hours to obtain solution b3 Add 1000 g of montmorillonite with a D50 of 400-500 nm to solution b, stir evenly, maintain the temperature at 100°C-110°C and dry under reduced pressure until constant weight, put into a 50L internal mixer, control the temperature at 120-130°C, plasticize under reduced pressure, and crush to obtain material c3; Divide material c3 into 2 parts on average, mix one part with 3kg of maleic anhydride grafted PP with a grafting rate of 1.2%, and then react and extrude it into granules. The temperature is controlled at 160℃-220℃ and the reaction time is 60-70 seconds to obtain colorable permanent antistatic masterbatch d31; the other part is mixed with 3kg of SMA-700 (maleic anhydride content of 18%) and then react and extrude it into granules. The temperature is controlled at 170℃-220℃ and the reaction time is 50-60 seconds to obtain colorable permanent antistatic masterbatch d32.
[0038] Example 4 600 g of PVA0588, 10000 g of deionized water, 1000 g of lithium p-methylstyrene sulfonate, appropriate amounts of catalysts such as ferric chloride, pentamethyldiethylenetriamine and ammonium chloride, and a molecular weight regulator such as 2-hydroxyethyl 2-bromoisobutyrate were placed in a 50 L reactor, stirred, and catalyzed by ultraviolet light. The reaction time was controlled to be 4-6 hours and the temperature was 25-30° C. to obtain a solution a4 of a lithium styrene sulfonate oligomer having a polymerization degree of 6 to 8. Add 400g of diethylene glycol, 600g of polyglycerol decaglycerol, and 50g of alcohol ether phosphate MOA-9P to solution a4, stir evenly, then add 11400g of PVA1799 resin and 10000g of deionized water, heat and stir to 60°C, keep warm for 30 minutes, then heat and stir to 95-100°C and keep warm for 1-2 hours to obtain solution b4 Add 1000 g of montmorillonite with a D50 of 400-500 nm to solution b4, stir evenly, maintain the temperature at 100°C-110°C and dry under reduced pressure until constant weight, put into a 50L internal mixer, control the temperature at 120-130°C, plasticize under reduced pressure, and crush to obtain material c4; Divide material c4 into 2 parts, one part is mixed with 3kg of maleic anhydride grafted PP with a grafting rate of 1.2%, and then reacted by extrusion granulation. The temperature is controlled at 160℃-220℃, and the reaction time is 60-70 seconds to obtain colorable permanent antistatic masterbatch d41; the other part is mixed with 3kg of SMA-700 (maleic anhydride content of 18%), and then reacted by extrusion granulation. The temperature is controlled at 170℃-220℃, and the reaction time is 50-60 seconds to obtain colorable permanent antistatic masterbatch d42.
[0039] Example 5 600 g of PVA0588, 10000 g of deionized water, 500 g of sodium p-methylstyrene sulfonate, 500 g of potassium p-methylstyrene sulfonate, appropriate amounts of catalysts such as ferric chloride, pentamethyldiethylenetriamine and ammonium chloride, and a molecular weight regulator such as 2-hydroxyethyl 2-bromoisobutyrate were placed in a 50 L reactor, stirred, and catalyzed by ultraviolet light. The reaction time was controlled to be 4-6 hours and the temperature was 25-30° C. to obtain a solution a5 of a potassium styrene sulfonate oligomer having a polymerization degree of 6 to 8. Add 400g of diethylene glycol, 600g of polyglycerol decaglycerol, and 50g of alcohol ether phosphate MOA-9P to solution a4, stir evenly, then add 11400g of PVA1799 resin and 10000g of deionized water, heat and stir to 60°C, keep warm for 30 minutes, heat and stir again to 95-100°C and keep warm for 1-2 hours to obtain solution b5 Add 1000 g of montmorillonite with a D50 of 400-500 nm to solution b5, stir evenly, maintain the temperature at 100°C-110°C and dry under reduced pressure until constant weight, put into a 50L internal mixer, control the temperature at 120-130°C, plasticize under reduced pressure, and crush to obtain material c5; Divide material c5 into 2 parts on average. Mix one part with 3kg of maleic anhydride grafted PP with a grafting rate of 1.2% and then react and extrude it into granules. The temperature is controlled at 160℃-220℃ and the reaction time is 60-70 seconds to obtain colorable permanent antistatic masterbatch d51. Mix the other part with 3kg of SMA-700 (maleic anhydride content of 18%) and then react and extrude it into granules. The temperature is controlled at 170℃-220℃ and the reaction time is 50-60 seconds to obtain colorable permanent antistatic masterbatch d52.
[0040] Example 6 600 g of PVA0588, 10000 g of deionized water, 1000 g of sodium p-methylstyrene sulfonate, appropriate amounts of catalysts such as ferric chloride, pentamethyldiethylenetriamine and ammonium chloride, and a molecular weight regulator such as 2-hydroxyethyl 2-bromoisobutyrate are placed in a 50 L reactor, stirred, and catalyzed by ultraviolet light. The reaction time is controlled to be 4-6 hours and the temperature is 25-30° C. to obtain a solution a6 of oligomers of sodium styrene sulfonate having a degree of polymerization of 6 to 8; Add 400 g of diethylene glycol, 600 g of polyglycerol decaglycerol, and 50 g of alcohol ether phosphate MOA-9P to solution a6, stir evenly, then add 11400 g of PVA0599 resin and 10000 g of deionized water, heat and stir to 60°C, keep warm for 30 minutes, heat and stir again to 95-100°C and keep warm for 1-2 hours to obtain solution b6; Add 1000 g of montmorillonite with a D50 of 400-500 nm to solution b6, stir evenly, maintain the temperature at 100°C-110°C and dry under reduced pressure until constant weight, put into a 50L internal mixer, control the temperature at 120-130°C, plasticize under reduced pressure, and crush to obtain material c6; Divide material c6 into 2 parts on average. One part is mixed with 3kg of maleic anhydride grafted PP with a grafting rate of 1.2%, and then reacted by extrusion granulation. The temperature is controlled at 160℃-220℃ and the reaction time is 60-70 seconds to obtain colorable permanent antistatic masterbatch d61. The other part is mixed with 3kg of SMA-700 (maleic anhydride content of 18%), and then reacted by extrusion granulation. The temperature is controlled at 170℃-220℃ and the reaction time is 50-60 seconds to obtain colorable permanent antistatic masterbatch d62.
[0041] Example 7 600 g of PVA0588, 10000 g of deionized water, 1000 g of sodium p-methylstyrene sulfonate, appropriate amounts of catalysts such as ferric chloride, pentamethyldiethylenetriamine and ammonium chloride, and a molecular weight regulator such as 2-hydroxyethyl 2-bromoisobutyrate were placed in a 50 L reactor, stirred, and catalyzed by ultraviolet light. The reaction time was controlled to be 4-6 hours and the temperature was 25-30° C. to obtain a solution of oligomers of sodium styrene sulfonate with a degree of polymerization ranging from 6 to 8. Add 500g of diethylene glycol, 500g of polyglycerol, and 50g of alcohol ether phosphate MOA-9P to solution a7, stir evenly, then add 11400g of PVA1799 resin and 10000g of deionized water, heat and stir to 60°C, keep warm for 30 minutes, then heat and stir to 95-100°C and keep warm for 1-2 hours to obtain solution b7 Add 1000 g of montmorillonite with a D50 of 400-500 nm to solution b6, stir evenly, maintain the temperature at 100°C-110°C and dry under reduced pressure to constant weight, put into a 50L internal mixer, control the temperature at 120-130°C, plasticize under reduced pressure, and crush to obtain material c7; Divide material c7 into 2 parts on average, mix one part with 3kg of maleic anhydride grafted PP with a grafting rate of 1.2%, and then react and extrude it into granules. The temperature is controlled at 160℃-220℃ and the reaction time is 60-70 seconds to obtain colorable permanent antistatic masterbatch d71; the other part is mixed with 3kg of SMA-700 (maleic anhydride content of 18%) and then react and extrude it into granules. The temperature is controlled at 170℃-220℃ and the reaction time is 50-60 seconds to obtain colorable permanent antistatic masterbatch d72.
[0042] Comparative Example 1 300 g of PVA0588, 10000 g of deionized water, and 1000 g of sodium p-methylstyrene sulfonate were placed in a 50 L reactor and stirred at a temperature of 25-30 ° C to obtain solution a8. Add 400g of diethylene glycol, 600g of polyglycerol decaglycerol, and 50g of alcohol ether phosphate MOA-3P to solution a8, stir evenly, then add 11700g of PVA1799 resin and 10000g of deionized water, heat and stir to 60°C, keep warm for 30 minutes, heat and stir again to 95-100°C and keep warm for 1-2 hours to obtain solution b8 Add 1000 g of montmorillonite with a D50 of 400-500 nm to solution b8, stir evenly, maintain the temperature at 100°C-110°C and dry under reduced pressure until constant weight, put into a 50L internal mixer, control the temperature at 120-130°C, plasticize under reduced pressure, and crush to obtain material c8; Divide material c8 into 2 parts, one part is mixed with 3kg of maleic anhydride grafted PP with a grafting rate of 1.2%, and then reacted by extrusion granulation. The temperature is controlled at 160℃-220℃, and the reaction time is 60-70 seconds to obtain colorable permanent antistatic masterbatch d81; the other part is mixed with 3kg of SMA-700 (maleic anhydride content of 18%), and then reacted by extrusion granulation. The temperature is controlled at 170℃-220℃, and the reaction time is 50-60 seconds to obtain colorable antistatic masterbatch d82.
[0043] Comparative Example 2 100 g of PVA0588, 10000 g of deionized water, 1000 g of sodium p-methylstyrene sulfonate, appropriate amounts of catalysts such as ferric chloride, pentamethyldiethylenetriamine and ammonium chloride, and a molecular weight regulator such as 2-hydroxyethyl 2-bromoisobutyrate were placed in a 50 L reactor, stirred, and catalyzed by ultraviolet light. The reaction time was controlled to be 4-6 hours and the temperature was 25-30° C. to obtain a solution of oligomers of sodium styrene sulfonate with a degree of polymerization of 25-30. Add 400g of diethylene glycol, 600g of polyglycerol decaglycerol, and 50g of alcohol ether phosphate MOA-3P to solution a9, stir evenly, then add 11900g of PVA1799 resin and 10000g of deionized water, heat and stir to 60°C, keep warm for 30 minutes, then heat and stir to 95-100°C and keep warm for 1-2 hours to obtain solution b9 Add 1000 g of montmorillonite with a D50 of 400-500 nm to solution b9, stir evenly, maintain the temperature at 100°C-110°C and dry under reduced pressure until constant weight, put into a 50L internal mixer, control the temperature at 120-130°C, plasticize under reduced pressure, and crush to obtain material c9; Divide material c9 into 2 parts, one part is mixed with 3kg of maleic anhydride grafted PP with a grafting rate of 1.2%, and then reacted by extrusion granulation. The temperature is controlled at 160℃-220℃, and the reaction time is 60-70 seconds to obtain colorable permanent antistatic masterbatch d91; the other part is mixed with 3kg of SMA-700 (maleic anhydride content of 18%), and then reacted by extrusion granulation. The temperature is controlled at 170℃-220℃, and the reaction time is 50-60 seconds to obtain colorable permanent antistatic masterbatch d92.
[0044] Comparative Example 3 600 g of PVA0588, 10000 g of deionized water, 1000 g of sodium p-methylstyrene sulfonate, appropriate amounts of catalysts such as ferric chloride, pentamethyldiethylenetriamine and ammonium chloride, and a molecular weight regulator such as 2-hydroxyethyl 2-bromoisobutyrate were placed in a 50 L reactor, stirred, and catalyzed by ultraviolet light. The reaction time was controlled to be 4-6 hours and the temperature was 25-30° C. to obtain a solution of oligomers of sodium styrene sulfonate with a degree of polymerization of 6-8. Add 400g of diethylene glycol, 600g of polyglycerol decaglycerol, and 50g of alcohol ether phosphate MOA-3P to solution a10, stir evenly, then add 11400g of PVA1799 resin and 10000g of deionized water, heat and stir to 60°C, keep warm for 30 minutes, then heat and stir to 95-100°C and keep warm for 1-2 hours to obtain solution b10 The solution b10 was kept at 100-110°C and dried under reduced pressure to constant weight, then put into a 50L internal mixer, controlled at 120-130°C, plasticized under reduced pressure, and crushed to obtain material c10; Divide material c10 into 2 parts on average. Mix one part with 3kg of maleic anhydride grafted PP with a grafting rate of 1.2% and then react and extrude it into granules. The temperature is controlled at 160℃-220℃ and the reaction time is 60-70 seconds to obtain colorable permanent antistatic masterbatch d101. Mix the other part with 3kg of SMA-700 (maleic anhydride content of 18%) and then react and extrude it into granules. The temperature is controlled at 170℃-220℃ and the reaction time is 50-60 seconds to obtain colorable permanent antistatic masterbatch d102.
[0045] Comparative Example 4 600 g of PVA0588, 10000 g of deionized water, 1000 g of sodium p-methylstyrene sulfonate, appropriate amounts of catalysts such as ferric chloride, pentamethyldiethylenetriamine and ammonium chloride, and a molecular weight regulator such as 2-hydroxyethyl 2-bromoisobutyrate were placed in a 50 L reactor, stirred, and catalyzed by ultraviolet light. The reaction time was controlled to be 4-6 hours and the temperature was 25-30° C. to obtain a solution of oligomers of sodium styrene sulfonate with a degree of polymerization of 6 to 8. Add 400g of diethylene glycol and 600g of polyglycerol to solution a11, stir evenly, then add 11400g of PVA1799 resin and 10000g of deionized water, heat and stir to 60°C, keep warm for 30 minutes, then heat and stir to 95-100°C and keep warm for 1-2 hours to obtain solution b11 Add 1000 g of montmorillonite with a D50 of 400-500 nm to solution b11, stir evenly, maintain the temperature at 100°C-110°C, dry under reduced pressure to constant weight, put into a 50L internal mixer, control the temperature at 120-130°C, plasticize under reduced pressure, and crush to obtain material c111; Divide material c11 into 2 parts on average, mix one part with 3kg of maleic anhydride grafted PP with a grafting rate of 1.2%, and then react and extrude it into granules. The temperature is controlled at 160℃-220℃, and the reaction time is 60-70 seconds to obtain colorable permanent antistatic masterbatch d11; the other part is mixed with 3kg of SMA-700 (maleic anhydride content of 18%), and then react and extrude it into granules. The temperature is controlled at 170℃-220℃, and the reaction time is 50-60 seconds to obtain colorable permanent antistatic masterbatch d112.
[0046] Please refer to Table 1 and Table 2 for the actual results.
[0047]
[0048] Table 2 The embodiments are exemplary and intended to be used to explain the present invention, but should not be construed as limiting the present invention. The embodiments should not be regarded as limiting the present invention, but any improvements made based on the spirit of the present invention should be within the scope of protection of the present invention.
Claims
1. An antistatic masterbatch, characterized in that: The following components are included by weight: 40 to 60 parts of PVA resin; Maleic anhydride graft or copolymer 10-40 parts 2-10 parts of organic alkali metal salt oligomer Plasticizer 10-15 parts Antidegradant 0.5~5 parts 3-7 parts of metal silicate or carbonate The rest are other additives.
2. The antistatic masterbatch and preparation method thereof according to claim 1, characterized in that: The PVA resin has an alcoholysis degree of 88%-100%, wherein the PVA with an alcoholysis degree of 88% accounts for 3%-6%, and the PVA with an alcoholysis degree of 99% accounts for 94%-97%.
3. The antistatic masterbatch and preparation method thereof according to claim 1, characterized in that: The metal silicate is a silicate of calcium, magnesium, aluminum, potassium, sodium or a carbonate of calcium, magnesium, aluminum, potassium, sodium.
4. The antistatic masterbatch and preparation method thereof according to claim 1, characterized in that: The monomer of the organic alkali metal salt oligomer is p-styrene sulfonate, and the alkali metal ion is one or more of Li+, Na+, and K+.
5. The antistatic masterbatch and preparation method thereof according to claim 1, characterized in that: The metal silicate is a mineral with a two-dimensional nanosheet structure.
6. The antistatic masterbatch and preparation method thereof according to claim 1, characterized in that: The plasticizer is one or a mixture of ethylene glycol and its polymers, propylene glycol and its polymers, and fatty amine polyoxyethylene ether.
7. A method for preparing the antistatic masterbatch according to claims 1-6, characterized in that: The following steps are involved: Step 1, preparing oligomers of styrene sulfonate: 3-6 parts of PVA, 100-200 parts of deionized water, and 10-30 parts of styrene sulfonate are added into a reactor, and the reaction time is controlled to be 4-6 hours and the temperature is 25-30° C. to obtain a solution a of oligomers of styrene sulfonate with a degree of polymerization ranging from 5 to 20; Step 2, add 10-30 parts of one or more mixtures of glycerol, ethylene glycol and polymers thereof, propylene glycol and polymers thereof and fatty amine polyoxyethylene ether, and 0.5-5 parts of alcohol ether phosphate to solution a, stir evenly, then add 94-97 parts of PVA resin, heat and stir to 50-70° C., keep warm for 30-60 minutes, heat and stir again to raise the temperature to 95-100° C. and keep warm for 1-2 hours to obtain mixture b; Step 3, add 1 to 20 parts of metal silicate or metal carbonate to solution b, stir evenly, maintain the temperature at 100°C and dry to constant weight, put into an internal mixer, control the temperature at 120-130°C, reduce pressure and plasticize, and crush to obtain material c; material c is mixed with 20-80 parts of maleic anhydride grafted or copolymerized polymer, and then reacted, extruded and granulated to obtain a colorable permanent antistatic masterbatch d.
8. The antistatic masterbatch and preparation method thereof according to claim 7, characterized in that: In the step 1, the polymerization degree of the oligomer of styrene sulfonate is 5 to 20; and the alcoholysis degree of PVA is 80% to 96%.
9. The antistatic masterbatch and preparation method thereof according to claim 8, characterized in that: The step 1 also includes a catalyst ferric chloride and a co-catalyst pentamethyldiethylenetriamine and ammonium chloride, and is catalyzed by ultraviolet light.
10. The antistatic masterbatch and preparation method thereof according to claim 9, characterized in that: The alcoholysis degree of the PVA resin in the step 3 is 99-100%.
Citation Information
Patent Citations
All-weather persistent antistatic master batch capable of being subjected to thermoplastic processing and antistatic composite material
CN102061050B